2002
DOI: 10.1128/jvi.76.22.11659-11676.2002
|View full text |Cite
|
Sign up to set email alerts
|

Both Mucosal and Systemic Routes of Immunization with the Live, Attenuated NYVAC/Simian Immunodeficiency Virus SIVgpeRecombinant Vaccine Result in Gag-Specific CD8+T-Cell Responses in Mucosal Tissues of Macaques

Abstract: As most human immunodeficiency virus (HIV) infection occurs via mucosal surfaces, an important goal of vaccination may be the induction of virus-specific immune responses at mucosal sites to contain viral infection early on. Here we designed a study in macaques carrying the major histocompatibility complex class I Mamu-A‫10ء‬ molecule to assess the capacity of the highly attenuated poxvirus NYVAC/simian immunodeficiency virus (SIV) SIV gpe vaccine candidate administered by the intranasal, intramuscular, or int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 54 publications
(39 reference statements)
7
55
0
Order By: Relevance
“…Furthermore, the validity of the nasal route of vaccination in the SIV model needs to be addressed. Nasal vaccination with attenuated NYVAC/SIVgpe stimulated significant antiviral responses in two female macaques, both systemically and at different mucosal sites (21). However, the number of animals in the group and the follow-up after challenge for only 48 h prevent the generalization of the results.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the validity of the nasal route of vaccination in the SIV model needs to be addressed. Nasal vaccination with attenuated NYVAC/SIVgpe stimulated significant antiviral responses in two female macaques, both systemically and at different mucosal sites (21). However, the number of animals in the group and the follow-up after challenge for only 48 h prevent the generalization of the results.…”
Section: Discussionmentioning
confidence: 90%
“…These studies represent important steps in the study of SIV DNA vaccines, but were not designed to evaluate mucosal immunity, and the challenge did not involve mucosal exposure. Only recently has SIV or simian/human immunodeficiency virus (SHIV) 3 DNA been investigated as a mucosal immunogen (21,23,36).…”
Section: S Tudies Of Virus-specific Immune Responses In Hiv-exposedmentioning
confidence: 99%
“…Indeed, several studies of rhesus macaques have demonstrated vaccine-induced functional SIV-specific CD8 T cells within the GI tract. 65,68,69 Moreover, the frequency of vaccine-induced SIV-specific CD8 T cells in the GI tract was negatively correlated with the peak viral load in plasma after challenge with the pathogenic SHIV-ku2, while there was no such correlation with the frequency of SIV-specific CD8 T cells in peripheral blood. 69 Although HIV-specific T-cell responses may reduce viral replication in vivo, the prevention of initial infection would likely require a mucosal humoral immune response.…”
Section: Gastrointestinal Hiv-specific Immune Responsesmentioning
confidence: 85%
“…11 and SI Table 2). Intramuscularimmunized animals exhibited mucosal immune responses as well, as seen in a previous intranasal immunization study (14). Because of variable sample sizes, sample compositions, and extents of cell expansions, significant intraanimal quantifications were not possible.…”
Section: -E)mentioning
confidence: 94%